Productivity potential of Eucalyptus grandis on soil of southeast Corrientes province and some soil characteristics involved in wood productivity - Aparicio, Jorge Luis; López, Juan Adolfo (Bosque (Valdivia), 1995)
Twenty six temporary plots were selected in 12-year-old commercial plantations of Eucalyptus grandis with the aim of evaluating its productivity potential on soils of the southeastern part of Corrientes Province. Thirty nine characters of tree growth, stem form, yield, and soil variables were determined from each site. A maximum of 597 m3 /ha for cellulosic purposes and of 537 m3 /ha for sawlog purposes could be obtained on the best sites. Electric conductivity, pH, available phosphorus in the A horizon, and percent of silt in the B horizon were the soil characteristics that showed greatest relationship with E. grandis productivity.